Peningkatan Kemampuan Berpikir Kritis Siswa: Sebuah Action Research - Lucky Nadya; Ridwan Santoso (Indonesian Journal Publisher, 2022)
This study aims to improve students' critical thinking skills on the subject of human activities in meeting needs. The learning design in this study uses a Problem Based Learning (PBL) model. The learning subjects of this study were 20 students. This research data collection technique was carried out systematically using observation sheets. Based on learning observations in the first cycle, students' critical thinking skills completeness only reached 35% and there are still 65% that have not been completed. In the second cycle, the students' critical thinking skills were 60% complete, but 40% were still incomplete. In the third cycle, the impact was able to improve students' critical thinking skills, which reached 85%. With the findings and observations from the first cycle to the third cycle there was a significant increase and reached the indicators of success set by the researcher. The results of this study prove that the application of the PBL learning model can improve students' critical thinking skills. This finding is expected to be a reference for educators to improve students' critical thinking skills.